Implementation of Discussion Methods Assisted by Audio Visual Media to Improve Student Activity and Learning Outcomes - Irsanti, Kurnia; Umi Kalsum (Yayasan Insan Mulia Bima, 2024)
This research was motivated by the researcher’s curiosity in using audio-visual learning media using the discussion method. This research is motivated by the low level of activity in the student learning process because the methods used are less varied and the media that supports learning has not been implemented optimally. The research method used in this article is a qualitative research method. Data collection techniques use interview, observation and documentation techniques. This type of media is able to provide a better learning experience because it includes sound and images. To support the success of this media, it must have adequate facilities and infrastructure that are suitable for use. A number of tools are used by teachers to convey concepts, ideas and experiences captured by the senses of sight and hearing based on the understandings that have been given. The use of audio-visual based learning media with discussion-based learning methods can increase the learning motivation of students in a less active learning process who pay attention to the lesson.